Sex Differences in Affective Facial Reactions Are Present in Childhood - Cattaneo, Luigi; Veroni, Vania; Boria, Sonia; Tassinari, Giancarlo; Turella, Luca (Frontiers in Integrative Neuroscience, 2018)
Adults exposed to affective facial displays produce specific rapid facial reactions (RFRs) which are of lower intensity in males compared to females. We investigated such sex difference in a population of 60 primary school children (30 F; 30 M), aged 7-10 years. We recorded the surface electromyographic (EMG) signal from the corrugator supercilii and the zygomatici muscles, while children watched affective facial displays. Results showed the expected smiling RFR to smiling faces and the expected frowning RFR to sad faces. A systematic difference between male and female participants was observed, with boys showing less ample EMG responses than age-matched girls. We demonstrate that sex differences in the somatic component of affective motor patterns are present also in childhood.